Rancangan Perangkat Lunak Aplikasi Perekam Data Kependudukan Dasar Desa - Nidia Rosmawanti; Muslihuddin Muslihuddin (Progresif: Jurnal Ilmiah Komputer, 2023)
The village population data processing information system is intended to increase efficiency in managing population data. So far, there are still many village governments who still manage population data using a manual system, which makes it difficult and slows down the process of adding or changing population data. This study aims to design basic population data recording application software at the village level, to provide convenience to employees in manipulating population data in order to provide efficiency in services. System development is carried out by following the initial stages in the system life cycle model (System Analysis and Design). Analysis of system requirements through in-depth interview techniques and focused discussions produces functional features to validate users, record citizen identities, record and print e-KTP applications, requests for birth and death certificates, requests for relocation. The results of the system requirements assessment are poured into a system model using a combination of structured and object-oriented modeling techniques.Keywords: System Modeling, Basic Population Data, Structured Modeling, Object Oriented ModelingAbstrakSistem informasi pengolahan data penduduk desa dimaksudkan untuk meningkatkan efisiensi dalam hal pengelolaan data kependudukan. Selama ini masih banyak pemerintah desa yang masih melakukan pengelolaan data kependudukan dengan sistem manual sehingga menyulitkan dan memperlambat dalam proses penambahan maupun perubahan data kependudukan. Penelitian ini bertujuan mendesain perangkat lunak aplikasi perekam data kependudukan dasar di tingkat Desa, untuk memberikan kemudahan kepada pegawai dalam melakukan manipulasi data kependudukan guna memberikan efisiensi dalam pelayanan. Pengembangan sistem dilakukan dengan mengikuti tahapan awal dalam model siklus hidup sistem (Analisis dan Desain Sistem). Kajian kebutuhan sistem melalui teknik wawancara mendalam dan diskusi terfokus menghasilkan fitur-fitur fungsional untuk memvalidasi pengguna, mendata identitas warga, mendata dan mencetak permohonan e-KTP, permohonan surat kelahiran dan kematian, permohonan pindah penduduk. Hasil kajian kebutuhan sistem di tuangkan dalam model sistem menggunakan kombinasi teknik pemodelan terstruktur dan berprientasi objek.Kata Kunci: Pemodelan Sistem, Data Kependudukan Dasar, Pemodelan Terstruktur, Pemodelan Berorientasi Objek